Emerging trends in urbanizing Palestine: neglected city-builders beyond the occupation. Issue 7 (9th August 2019) - Chitti, Marco; Moser, Sarah
ABSTRACT: In this article, we draw attention to trends in land transformation in the West Bank since the Second Intifada, after which a surge of investment from Gulf countries entered Palestine, almost exclusively in the West Bank. The occupied Palestinian territories have attracted a great deal of attention from media and academics, yet the vast majority of scholarship focuses on the conflict and the variety of social, economic, and political repercussions of the on-going Israeli occupation. While the occupation has undeniably serious impacts on every aspect of life for Palestinians, the near-exclusive focus on the conflict means that significant new trends, such as urban mega-developments and emerging market-based urbanisation processes, have been largely overlooked. We outline three directions for future research: the assemblage of "neglected city-builders" shaping current urbanization processes in Palestine; the ideas, policies, and norms circulating in the West Bank; and the social, spatial, economic, and other impacts of these new urban developments.